International financial law : lending, capital transfers, and institutions - Rendell, Robert S. (London : Euromoney, 1980)
-The studies collected in this volume draw attention ot the fact that international finance and investment are regulated through a machinery of control which mixes national and international elements. And the ordering of international fiscal relations is, as well, partly public and partly private. The lawyer cannot operate soley within the domain of law; he must know international commercial practice aand procedures. In this area of the law, the economist, the banker, the broker, the trader, and the lawyer must work together, and each must have some knowledge of the concerns and potential contributions of the other occupations. The lawyer is thus called upon to deal in a large way with the procedures and legal rules established for the regulation of both the international economy and various national economies.
Keywords: Loans, Foreign -- Law and legislation; Investments, Foreign -- Law and legislation; Foreign exchange -- Law and legislation; Banks and banking, International -- Law and legislation; Development banks -- Law and legislation